Optimal dose of granisetron in reducing the incidence and severity of pruritus post intrathecal morphine for Caesarean deliveries: Granisetron for pruritus post intrathecal morphine - Tong, Chong Ling; Ooi, Joanna; Kamaruzaman, Esa (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Pruritus is one of the common side effects observed after intrathecal morphine (ITM) especially among parturients. Granisetron, a 5-HT3 antagonist has been shown to reduce this side effect. MATERIAL AND METHODS: This prospective randomised double-blind control trial compared two different doses of granisetron for anti-pruritic efficacy. One hundred and twenty parturients with a singleton uncomplicated pregnancy undergoing Caesarean section received spinal anaesthesia with ITM 0.1 mg. After the delivery of baby, they were randomised to receive either granisetron 1 mg (Group 1) or 3 mg (Group 2). The severity of pruritus was assessed within 24 hours at different intervals and were graded. RESULTS: Patients demographic and clinical characteristics were comparable between the two groups. The incidence for pruritus between Group 1 and 2 was 63.3% and 65.0% respectively with p value of 0.849 with a proportion of difference of 1.7%. Similarly, the severity of pruritus at different intervals, the need for rescue treatment and patient satisfaction for both groups were not statistically significant. CONCLUSION: Granisetron 1mg is effective when given as prophylaxis in reducing the incidence, severity and the need for rescue treatment in ITM-induced pruritus among Caesarean delivery patients.